Biceps Brachii muscle contraction during different driving postures - Darliana Mohamad; Baba Md. Deros; Dian Darina Indah Darius; Ahmad Rasdan Ismail
This study was conducted to analysesthe Biceps Brachii (BB) muscle contraction during different driving postures. Drivers’ posture is one of the factors that contribute to driving fatigue that eventually may lead to road accident and injuries. The experiment conducted forthis study is using the surface electromyography (SEMG) method for objective evaluation of muscle involved in driving activities. A total of 14 participants are involved in the experiment. The experiment was done on three different posture based on comfortable angles published by previous research. From the results analysis, the RMS value for activity left turn is lower than activity for right turn for all three postures and results also shows that posture B with elbow angle of 134° is perceived as most comfortable based on the lowest value of muscle contractionwith a value of 15.67μV. The outcomesfrom this study are hoped to benefit both manufactures and also car users in ensuring better and optimum driving postures that can avoid fatigue and injuries